Macroeconomics and the Australian economy recent performance and challenges of the 1990s - Rogers, Colin (Prentice Hall, 1994)
Textbook for intermediate macroeconomics and applied macroeconomics courses. The Mundell-Fleming model and the Bruno Sachs analysis are used to derive an aggregate demand-aggregate supply model which is them used to examine macroeconomic policy. Current policy issues confronting Australia including economic rationalism, government budget deficits, foreign debt, unemployment, deregulation of the financial markets, enterprise bargaining and the macroeconomic consequences of microeconomic reform are covered.